Histopathological Changes in the Kidney following Congestive Heart Failure by Volume Overload in Rats - Noureddin B. Aboryag (Oxidative Medicine and Cellular Longevity, 2017)
Background. This study investigated histopathological changes and apoptotic factors that may be involved in the renal damage caused by congestive heart failure in a rat model of infrarenal aortocaval fistula (ACF). Methods. Heart failure was induced using a modified approach of ACF in male Wistar rats. Sham-operated controls and ACF rats were characterized by their morphometric and hemodynamic parameters and investigated for their histopathological, ultrastructural, and apoptotic factor changes in the kidney. Results. ACF-induced heart failure is associated with histopathological signs of congestion and glomerular and tubular atrophy, as well as nuclear and cellular degeneration in the kidney. In parallel, overexpression of proapoptotic Bax protein, release of cytochrome C from the outer mitochondrial membrane into cell cytoplasm, and nuclear transfer of activated caspase 3 indicate apoptotic events. This was confirmed by electron microscopic findings of apoptotic signs in the kidney such as swollen mitochondria and degenerated nuclei in renal tubular cells. Conclusions. This study provides morphological evidence of renal injury during heart failure which may be due to caspase-mediated apoptosis via overexpression of proapoptotic Bax protein, subsequent mitochondrial cytochrome C release, and final nuclear transfer of activated caspase 3, supporting the notion of a cardiorenal syndrome.